(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
تبين من النتائج أن الكثافة الظاهرية للتربة في المعاملة 400 ميلبار زادت معنوياً في العمق 0-20 سم بمقدار 0.23 غ/سم3 بعد سنتين من تنفيذ البحث . وفي العمق 20-40 سم زادت قيمة الكثافة بمقدار0.08 غ/سم3. في العمق 40-60 سم زادت بمقدار 0.06 غ/سم3. ولم تتغير معنويا في المعاملة 800 و1400 ميليبار. أما حجم المسامات الهوائية > 10 ميكرون انخفض بمقدار 9.65% في العمق 0-20 سم في المعاملة 400 ميلبار وانخفض بمقدار 4.26% في العمق 20-40 سم وبمقدار 3.81% في العمق 40-60 سم وازداد حجم هذه المسامات في المعاملة 800-1400 ميلبار بمقدار 5.21 -3.38 % على التوالي في العمق 40-60 سم . كانت أفضل إنتاجية للشجرة الواحدة كمتوسط لعامين متتالين عند شد رطوبي 900 ميلبار في العمق 30سم وضمن مجال شد رطوبي 600- 1250 ميليبار. أما إنتاجية المعاملة المتدرجة كانت أقل معنوياً من المعاملة 800-950 ميلبار ولكنها لم تختلف معنوياً عن المعاملة 1400 ميلبار . Results of this research showed that the apparent density of soil increased significantly in the treatment 400 millibars in depth of 0-20 cm by 0.23g/cm3 after two years, in comparison with the primary value. In depth of 20-40 cm, the density value increased in the treatment 400 millibars after two years by 0.08g/cm3. In depth of 40-60 cm, the density increased significantly in the treatment 400 millibars by 0.06g/cm3, millbars; but it did not differ immaterially in the treatment800-1400 millibars. The volume of the pores >10 microns after two years decreased significantly by 9.65% in the treatment 400 millibars and decrease by 4.26% in depth of 20-40 cm, and by 3.81%, in depth 40-60 cm and increased in the treatment800-1400 millibars by 5.21-3.38% respectively in the depth 40-60 cm. The best productivity per tree as an average of two consecutive years was at moisture tension of 900 millibars in depth of 30 cm, and within moisture tension range of 600-1250 millibars. The productivity of the graduated treatment as an average of two consecutive years was less immaterially than the treatment 800-950 millibars; but did not differ immaterially from the treatment 1400 millibars